Permanent Pacemaker-Mediated Exertional Hypoxemia in a Patient With Ebstein Anomaly - Ashish H. Shah, MD; Nasir Shaikh, MD; Keivan Alizadeh, MD; Aliasgar Khadem, MD; Clarence Khoo, MD; Robin A. Ducas, MD; Malek Kass, MD (JACC: Case Reports, 2024)
Patients with Ebstein anomaly are known to have a higher incidence of interatrial communications and shunting of blood and its components through, mainly due to either streaming of tricuspid regurgitation or due to elevated right atrial pressure. Here we describe a case where permanent pacemaker lead kept a patent foramen ovale open leading to right-to-left shunting of blood and exertional hypoxemia. This is the first such case report in the published literature.